Exchange rate uncertainty, futures markets and the multinational firm - Udo Broll; Itzhak Zilcha (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
We consider a monopolistic, risk-averse multinational firm which sells and produces at home and abroad under exchange rate uncertainty. First we show that the stochastic exchange rate implies higher production and lower sales in the foreign country. Then we analyze the impact of currency futures markets. A separation result is obtained for a multinational firm, i.e., production and the allocation of sales are independent of the distribution of the random exchange rate and of the firm's attitude towards risk. We also examine the effect of currency futures on a multinational firm's foreign direct investments. In the absence of futures markets we obtain some comparative statics results when risk aversion increases.
Keywords: 330